Le rôle de la gestion des approvisionnements sur la performance du projet: Étude de cas d’un échantillon de projets de construction de la wilaya de Constantine: The role of procurement management on project performance: Case study a sample of construction projects of the city of Constantine - Razkallah, Hanane; Bendjama, Rachida (Finance and Business Economies Review, 2022)
The project manager often seeks to identify methods that will help him get better performance from his project. As a contribution in this regard, this article reports a theoretical conceptual framework that illustrates the relationship between procurement management and project performance based on procurement stages such as planning, execution and the closure of the project in order to know what is the nature of relationship that may have existed between each stage of the procurement and the performance of the project. At the same time, an investigative process was adopted to shed light on the reality of this relationship in the construction projects of the city of Constantine. We arrived at several results, among them: despite the project managers respecting the axes of the project planning and archiving the information of the project during its closure for future use, most of the projects are not delivered within the planned deadlines, even the expenses that are spent to carry out the projects are not in accordance with the planned (planned) budget. This may be due to the absence of a control system that keeps track of the requirements and expectations of the customers agreed in the specifications.